The role of integrated management in the realization of intelligent transportation (Case study: Zahedan city) - Amir Kaveh; Maryam Karimian Bostani; Gholam reza Miri (تحقیقات کاربردی علوم جغرافیایی)
Along with the development of cities and increasing population, many challenges have been created, the most important of which is urban transportation. The inability of traditional urban management to address this challenge has led to some approaches, including intelligent transportation. Adopting and implementing such an approach in metropolitan areas requires a change in management approach, of which integrated urban management is known as the most important. The purpose of this study is to investigate the status of integrated urban management and then its impact on the realization of intelligent transportation in the city of Zahedan. The research method is descriptive-analytical and based on data collection in the field through a questionnaire. The validity of the instrument and its reliability was confirmed by Cronbach's alpha greater than 0.70. The statistical population of the study is urban experts in Zahedan. The sample size was set at 100 people. The result of the one-sample t-test shows that the variables of integrated urban management are significant at the level of less than 0.05. From the statistical point of view, the 7 variables of good governance, synergy, unity of urban command, context, interaction, organizational structure, and systemic perspective are not in a good situation and these conditions have caused the integrated urban management index in Zahedan to not have favorable conditions. Also, the significance of the test shows that the 5 variables of intelligent transportation, namely intelligent monitoring, intelligent payment, intelligent violation registration, intelligent information, and mechanized fleet management are significant at the level of less than 0.05. Significantly, it indicates the unfavorable situation of the intelligent transportation index in Zahedan. Regression showed that integrated urban management variables can be more than 68% effective in the realization of intelligent transportation and 32% are dependent on other factors. The variable of good governance with 12% and then the systemic perspective with 11%, has the greatest impact in this regard.